Impactos econômicos do manejo agroecológico da caatinga em unidades de produção familiar no Oeste Potiguar - Barreto, Hilton Felipe Marinho (2010)
The objective of this study was evaluated the economic impacts by the agroecological handling of caatinga in units of familiar production in the western potiguar-Brazil. The assay was lead in Apodi city, between 2009 and 2010, through interviews, for information collection of the referring the annual global relative prescription, annual global relative expenditure and annual relative liquid profit, the seven familiar agriculturists who used during two years the Agroecological Handling of the Caatinga. The indices was composed using the sales had been taken, how much the parcel of the production destined to themselves and recicle, as well as the referring expenditures only to the cattle breeding business that adopted handling. In the carried through analyses relations between the experience of the agriculturist in the agroecological handling had not been found and the percentage of the area of this handling in relationtotal area of the property. These result can have been influenced for the financial condition and assistance technique. Observed an average profit of R$ 724,19/ha in the units prescription, after the handling implantation, as well as had a bigger diversification of the cattle breeding business, mainly stimulating the ovinocultura and the beekeeping. This diversification more than provided an increment in the prescription of 140% and raising its liquid profitsin more of 269%. These results show that the use of the handling contributed for the monetary increment in the familiar units studied, configuring itself as generating of positive impacte, therefore, indicated for application for familiar agriculture